PARENTAL EMOTIONAL COACHING UNTUK MENINGKATKAN GAYA PENGASUHAN DAN PENERIMAAN ORANG TUA YANG MEMILIKI ANAK TUNARUNGU - Kusnadi, Starry Kireida; Agustin, Ardianti (Jurnal Psikologi Teori dan Terapan, 2019)
This study was aimed to determine the effect of parental emotional coaching on the improvement of the parenting style and parents? acceptances towards their deaf children. The population of this study was parents who have deaf children at Special Primary  School B 'X' Surabaya. There were 9 subjects involved in this study. This study employed an experimental method with one group pretest-posttest design. Data were collected using parenting style and parent?s acceptance scales and analyzed using Wilcoxon Signed Rank Test. The result shows that the value of Z = -2,668 with the asymp value of sig = 0.008 (p <0.05). It can be concluded from the result that parental emotional coaching training increases positive parenting style and parents? acceptances towards their deaf children. Keywords: Parental emotional coaching, parenting style, acceptance, deaf children